Plasmonic modification of electron-longitudinal-optical phonon coupling in Ag-nanoparticle embedded InGaN/GaN quantum wells - Llopis, Antonio (2014)
Surface plasmon enhanced GaN and InGaN quantum wells (QWs) show promise for use as room-temperature light emitters. The effectiveness of the plasmon enhancement, however, is limited by the strong electron/hole and longitudinal optical phonon coupling found in the III-V nitrides. The electron-phonon coupling within semiconductor QWs has been modified using silver nanoparticles embedded within the QWs. Direct evidence is provided for this change via confocal Raman spectroscopy of the samples. This evidence is augmented by Angle-dependent photoluminescence experiments which show the alteration of the electron-phonon coupling strength through measurement of the emitted phonon replicas. Together these demonstrate a direct modification of carrier-phonon interactions within the system, opening up the possibility of controlling the coupling strength to produce high-efficiency room-temperature light emitters. (C) 2014 AIP Publishing LLC.